Selective screening of secretory vesicle-associated proteins for autoantigens in type 1 diabetes VAMP2 and NPY are new minor autoantigens - Hirai, Hiroki (Clinical immunology (Orlando, Fla.), 2008)
The four major autoantigens (IA-2, IA-2 beta, GAD65 and insulin) of type 1 diabetes are all associated with dense core or synaptic vesicles. This raised the possibility that other secretory vesicle-associated proteins might be targets of the autoimmune response in type 1 diabetes. To test this hypothesis 56 proteins, two-thirds of which are associated with secretory vesicles, were prepared by in vitro transcription/translation and screened for autoantibodies by liquid phase radioimmunoprecipitation. Two secretory vesicle-associated proteins, VAMP2 and NPY, were identified as new minor autoantigens with 21% and 9%, respectively, of 200 type 1 diabetes sera reacting positively. These findings add support to the hypothesis that secretory vesicle-associated proteins are particularly important, but not the exclusive, targets of the autoimmune response in type 1 diabetes. Selective screening of the human proteome offers a useful approach for identifying new autoantigens in autoimmune diseases